Substrate with film and method for producing the same

JP2025041257APending Publication Date: 2025-03-26AGC INC

Patent Information

Application Number
JP2023148445
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-13
Publication Date
2025-03-26

Smart Images

  • Figure 2025041257000001_ABST
    Figure 2025041257000001_ABST
Patent Text Reader

Abstract

To provide a substrate with a film that reduces uneven transmission and homogenizes brightness and contrast and to provide a method for producing the same.SOLUTION: This invention relates to a substrate with a film comprising a main material and a film disposed on the main material, wherein the main material is a glass and has a first surface and a second surface opposite each other; the film is located on the first surface of the main material and comprises a visible light absorption layer made of a doped metal oxide doped with impurity elements; and two or more peaks are verified where impurities concentration is at its maximum, when a concentration distribution of the impurities in a film thickness direction of the visible light absorption layer is measured using X-ray photoelectron spectroscopy.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a film-coated substrate and a method for producing the same. [Background technology]

[0002] 2. Description of the Related Art Film-attached substrates, such as glass substrates with a thin film and films with a thin film, are widely used in various fields as materials that satisfy various required properties by laminating a functional film onto the main material, such as glass or film.

[0003] For example, in the window glass used in vehicles and buildings, low-emissivity glass (Low-E glass) with heat insulating and heat shielding properties is used due to the recent increase in energy saving awareness. Low-emissivity glass is constructed by laminating one or more functional layers made of metal oxides or the like on a glass substrate, and includes, as the functional layers, for example, a heat ray reflecting layer, a heat ray absorbing layer, a visible light reflecting layer, a visible light absorbing layer, an optical adjustment layer, and the like.

[0004] In applications such as vehicles and buildings, the film-coated substrate may be required to have a dark color, i.e., a relatively low visible light transmittance, for privacy protection, and in such cases, it is preferable to provide a visible light absorbing layer as a functional layer. A visible light absorbing layer may also be provided as a layer that has both heat insulation properties and visible light absorbing properties.

[0005] One method for forming the functional layer is known to be the chemical vapor deposition (CVD) method. For example, Patent Documents 1 and 2 describe the formation of a laminated film on a glass ribbon in an annealing furnace by the online CVD method. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2013 / 008894 [Patent Document 2] International Publication No. 2014 / 112482 Summary of the Invention [Problem to be solved by the invention]

[0007] However, when a film-coated substrate including a visible light absorbing layer as a functional layer is formed by a CVD method, striped unevenness in transmittance (hereinafter also referred to as transmission unevenness) may occur when the obtained film-coated substrate is held up to light and the transmitted light is observed.

[0008] Therefore, an object of the present invention is to provide a film-coated substrate in which uneven transmission is reduced and brightness and contrast are homogenized, and a method for producing the same. [Means for solving the problem]

[0009] As a result of intensive research, the present inventors have found that the above-mentioned problems can be solved by using two or more coaters when forming a visible light absorbing layer by a CVD method, and have completed the present invention. In addition, when a film-attached substrate on which a visible light absorbing layer made of a doped metal oxide doped with an impurity element is formed by the above-mentioned method is measured for the impurity concentration distribution in the thickness direction of the visible light absorbing layer by X-ray photoelectron spectroscopy, it has been found that two or more peaks at which the impurity concentration is maximum are confirmed.

[0010] That is, the present invention relates to the following (1) to (6). (1) A film-coated substrate comprising a main material and a film disposed on the main material, the main material being glass, the main material having a first surface and a second surface opposing each other, the film being located on the first surface of the main material, the film including a visible light absorbing layer made of a doped metal oxide doped with an impurity element, and when an impurity concentration distribution in a thickness direction of the visible light absorbing layer is measured by X-ray photoelectron spectroscopy, two or more peaks at which the impurity concentration is maximized are confirmed. (2) The film-coated substrate according to (1) above, wherein the visible light absorbing layer is an antimony-doped tin oxide film. (3) The film-coated substrate according to (1) or (2) above, wherein the film-coated substrate has a light source A transmittance of less than 30%. (4) A method for producing a film-coated substrate, comprising forming a film on a main material, the main material being glass, and comprising forming a visible light absorbing layer by a thermal CVD method on a production line for the glass, the visible light absorbing layer being formed using two or more coaters. (5) The method for producing a film-coated substrate according to (4) above, wherein the visible light absorbing layer is made of a doped metal oxide doped with an impurity element. (6) The method for producing a film-coated substrate according to (4) or (5) above, wherein the light source A transmittance of the obtained film-coated substrate is less than 30%. Effect of the Invention

[0011] The film-coated substrate of the present invention has reduced transmission unevenness and is visually clear and has excellent aesthetics, and can therefore be suitably used for glass members of vehicles, buildings, and the like.

[0012] According to the method for producing a film-coated substrate of the present invention, it is possible to produce a film-coated substrate with reduced transmission unevenness and excellent appearance. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a cross-sectional view of a film-coated substrate for illustrating the configuration of one embodiment of the film-coated substrate of the present invention. [Diagram 2] FIG. 2 is a diagram showing examples of impurity concentration distribution in the film thickness direction of a visible light absorbing layer, where (a) is a diagram showing the impurity concentration distribution in the visible light absorbing layer of the film-coated substrate prepared in Example 1, (b) is a diagram showing the impurity concentration distribution in the visible light absorbing layer of the film-coated substrate prepared in Example 5, and (c) is a diagram showing the impurity concentration distribution in the visible light absorbing layer of the film-coated substrate prepared in Example 6. [Diagram 3] FIG. 3 is a cross-sectional view of a film-coated substrate for illustrating the configuration of another embodiment of the film-coated substrate of the present invention. [Figure 4] FIG. 4 is a diagram that illustrates a schematic diagram of an example of a production apparatus used in the method for producing a film-coated substrate of the present invention. [Diagram 5] FIG. 5 is a diagram showing a schematic configuration example of a coater. [Figure 6] FIG. 6 is a diagram for explaining a method of photographing a sample to obtain the contrast ratio. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present invention will be described in detail below, but the present invention is not limited to the following embodiments, and can be modified as desired without departing from the gist of the present invention. In addition, the use of "to" to indicate a numerical range means that the numerical values ​​before and after the range are included as the lower and upper limits. Note that the embodiments shown in the drawings are schematic in order to clearly explain the present invention, and do not necessarily accurately represent the actual size or scale.

[0015] (Substrate with film) A film-coated substrate according to an embodiment of the present invention is a film-coated substrate comprising a main material and a film disposed on the main material, the main material being glass, the main material having a first surface and a second surface opposing each other, the film being located on the first surface of the main material, the film including a visible light absorbing layer made of a doped metal oxide doped with an impurity element, and when an impurity concentration distribution in a thickness direction of the visible light absorbing layer is measured by X-ray photoelectron spectroscopy, two or more peaks at which the impurity concentration is maximized are confirmed.

[0016] In the film-attached substrate according to the embodiment of the present invention, the visible light absorbing layer is made of a doped metal oxide doped with an impurity element, and when the impurity concentration distribution in the film thickness direction of the visible light absorbing layer is measured by X-ray photoelectron spectroscopy, two or more peaks of maximum impurity concentration are confirmed, which means that the visible light absorbing layer is formed by CVD using two or more coaters. This suppresses the transmission unevenness of the film-attached substrate according to the embodiment of the present invention, and provides excellent aesthetics.

[0017] 1, a film-coated substrate 10 which is one embodiment of the film-coated substrate of the present invention, comprises a main material 1 and a film 2 disposed on the main material 1. The main material 1 has a first surface 1a and a second surface 1b which face each other, and the film 2 is disposed on the first surface 1a of the main material 1. In this embodiment, the film 2 includes a visible light absorbing layer 3. The film 2 may be one layer or a laminated film consisting of two or more layers. When the film 2 is two or more layers, it may have multiple visible light absorbing layers 3 of different compositions, or may have other functional layers. In this embodiment, the visible light absorbing layer is formed using two or more coaters, but when the visible light absorbing layer is "one layer", it means that the visible light absorbing layer is one layer formed by continuously stacking layers of substantially the same composition using two or more coaters. When the continuously stacked layers are "layers of substantially the same composition", it means that the layers of the same composition are stacked without intentionally changing the composition. In other words, when the composition is not intentionally changed but the composition distribution in the thickness direction inevitably changes slightly due to the film formation using two or more coaters, it is judged to be "layers of substantially the same composition". For example, when the metal oxide species constituting the layers are the same and the difference in impurity concentration is 5 mol% or less, it can be judged to be "layers of substantially the same composition".

[0018] (Main material) The main material 1 serves as the skeleton of the film-coated substrate 10 and has self-supporting properties. The main material of the film-coated substrate according to this embodiment is glass.

[0019] Examples of glass include soda lime silicate glass, aluminosilicate glass, borate glass, lithium aluminosilicate glass, quartz glass, borosilicate glass, and alkali-free glass.

[0020] The main material can be selected to be transparent, translucent, or opaque depending on the application and purpose of the film-coated substrate. The main material may be colorless or colored. In particular, when colorless and transparent glass is used as the main material, it becomes unnecessary to add impurities during glass production, improving productivity. Specifically, colorless and transparent refers to the main material having a visible light transmittance (T L, the visible light transmittance measured in accordance with ISO 9050:2003) is 85% or more.

[0021] When using a colorless and transparent base material, the visible light transmittance (T L ) is preferably 85% or more, more preferably 86% or more, even more preferably 87% or more, and particularly preferably 88% or more. From the viewpoint of clarity, the higher the transmittance, the better, so there is no particular upper limit.

[0022] The shape of the main material is not particularly limited, and may be a plate, a film, a sheet, etc., and may be any shape depending on the intended use. For example, a plate shape is preferable for use in vehicle members and building members.

[0023] The thickness of the main material may be appropriately adjusted depending on the application and purpose of the film-coated substrate. For example, when the film-coated substrate is used for vehicle members, the thickness of the main material is preferably 5 mm or less, more preferably 4.5 mm or less, even more preferably 3.8 mm or less, particularly preferably 2.8 mm or less, and is preferably 1 mm or more, more preferably 1.3 mm or more, and even more preferably 1.6 mm or more. That is, the thickness of the main material is preferably 1 to 5 mm for vehicle member applications. When the membrane-coated substrate is used as a building component, the thickness of the main material is preferably 4 to 12 mm, more preferably 4.1 mm or more, even more preferably 5.1 mm or more, and more preferably 10 mm or less, even more preferably 8 mm or less.

[0024] The size (area) of the main material is not particularly limited, and may be appropriately adjusted depending on the application and purpose of the film-coated substrate. For example, when using a substrate with a membrane for a vehicle, the area of ​​the main surface of the main material is 0.5 to 5 m 2 When the membrane-coated substrate is used in a building, the area of ​​the main surface of the main material is preferably 0.5 to 10 m. 2 It is preferable that:

[0025] (film) In the film-coated substrate 10 of the present invention, the film 2 laminated on the base material 1 includes a visible light absorbing layer 3 .

[0026] <Visible light absorbing layer> The visible light absorbing layer 3 is a layer that reflects solar heat and provides the film-coated substrate with heat shielding properties, and has crystallinity. The visible light absorbing layer 3 has the above-mentioned heat shielding properties and also has visible light absorbing properties.

[0027] When various functional layers are formed by the CVD method, there may be unevenness in the film thickness depending on the position on the film formation surface, but the more visible light absorbing the layer is, the greater the transmission unevenness is likely to be due to the unevenness in the film thickness. Therefore, the film-attached substrate having a visible light absorbing layer is likely to have transmission unevenness. In contrast, in the present invention, it has been found that the visible light absorbing layer is formed using two or more coaters, which suppresses transmission unevenness and provides excellent aesthetics.

[0028] The visible light absorbing layer is made of a doped metal oxide doped with an impurity element. By forming the visible light absorbing layer from a doped metal oxide, it is possible to impart a desired function to the visible light absorbing layer.

[0029] Examples of metal oxides include tin oxide, indium oxide, zinc oxide, titanium oxide, niobium oxide, and tantalum oxide. Examples of impurity elements that may be doped into the doped metal oxide include antimony, fluorine, tin, potassium, aluminum, tantalum, niobium, nitrogen, boron, indium, and carbon.

[0030] In the visible light absorption layer made of a doped metal oxide, the concentration of the doped impurity element may be appropriately set depending on the impurity element, but is preferably in the range of 0.1 to 30 mol%. If the concentration of the impurity element is 0.1 mol% or more, the transmittance of the film-coated substrate can be easily reduced to a predetermined value, and if it is 30 mol% or less, the crystal structure before doping can be maintained.

[0031] In the present invention, the visible light absorbing layer is preferably provided with a film made of antimony-doped tin oxide (ATO, a metal oxide in which Sb is added to SnO2). The antimony-doped tin oxide film reduces the amount of heat transferred to the inside of the substrate, and provides the substrate with the film with excellent heat insulation properties.

[0032] The antimony concentration in the visible light absorbing layer is preferably 10 to 30 mol%. When the antimony concentration in the visible light absorbing layer is 10 mol% or more, heat shielding properties can be exhibited, and when the antimony concentration is 30 mol% or less, the crystal structure before doping can be maintained. The antimony concentration in the visible light absorbing layer is more preferably 12 mol% or more, even more preferably 14 mol% or more, particularly preferably 16 mol% or more, and more preferably 25 mol% or less, even more preferably 23 mol% or less, particularly preferably 20 mol% or less.

[0033] In the substrate with film according to the embodiment of the present invention, when the visible light absorbing layer is made of doped metal oxide containing impurity elements, when the impurity concentration distribution in the thickness direction of the visible light absorbing layer is measured by X-ray photoelectron spectroscopy, two or more peaks of maximum impurity concentration are confirmed. As mentioned above, this means that the visible light absorbing layer is formed by the CVD method using two or more coaters.

[0034] The composition of the visible light absorption layer and the concentration of the doped impurity element can be identified by X-ray photoelectron spectroscopy (XPS) or secondary ion mass spectrometry (SIMS). For example, the antimony (Sb) concentration in an antimony-doped tin oxide film is determined by depth analysis using X-ray photoelectron spectroscopy (XPS) and the intensity ratio of Sb to Sn. The fluorine (F) concentration in a fluorine-doped tin oxide film is determined by depth analysis using secondary ion mass spectrometry (SIMS) and the intensity ratio of F to Sn. When using SIMS, fluorine-doped tin SnO2 with a known concentration is measured and a coefficient is found to convert the F / Sn intensity ratio into concentration. The concentration of impurity elements in the visible light absorption layer is determined by averaging the concentrations in the depth direction of the measured layer. Here, the peak where the impurity concentration is maximum when the impurity concentration distribution in the thickness direction of the visible light absorption layer is measured by X-ray photoelectron spectroscopy refers to a mountain when the impurity concentration distribution in the thickness direction is measured, but does not include a mountain where the peak is at the film surface.

[0035] FIG. 2 shows an example of the impurity concentration distribution in the thickness direction of the visible light absorbing layer by X-ray photoelectron spectroscopy. (a) to (c) of FIG. 2 are diagrams showing the impurity concentration distribution in the thickness direction of the visible light absorbing layer (antimony-doped tin oxide film) formed by the CVD method. The visible light absorbing layer in FIG. 2 (a) is formed using one coater, and the visible light absorbing layers in FIG. 2 (b) and (c) are formed using two coaters, respectively. In FIG. 2 (a) to (c), as shown by the arrows in the figure, peaks where the impurity concentration is maximum can be confirmed. In FIG. 2 (a) where one coater was used, there is one peak, and in FIG. 2 (b) and (c) where two coaters were used, there are two peaks. From these, it can be seen that if two or more peaks where the impurity concentration is maximum are confirmed when the above impurity concentration distribution is measured, it can be determined that the visible light absorbing layer is formed by the CVD method using two or more coaters.

[0036] The substrate with film of the present invention has a visible light absorbing layer formed by CVD using two or more coaters, that is, two or more peaks of maximum impurity concentration are confirmed in the above impurity concentration distribution, so that transmission unevenness is suppressed.The reason for this is that, even if a layer with a relatively low visible light transmittance is formed using two or more coaters, and thickness unevenness and transmission unevenness due to it occur, the unevenness is homogenized due to the different patterns of unevenness caused by each coater, and as a result, the thickness unevenness of the visible light absorbing layer obtained is reduced.

[0037] The visible light absorbing layer may be one layer, or may be two or more layers of films with different materials, metal contents, etc. Within the range where the effects of the present invention can be obtained, one layer of film may be formed by two or more coaters, or two or more layers of film may be formed by two or more coaters. From the viewpoint of more suitably suppressing uneven transmission, it is preferable to form one layer of film by two or more coaters. For example, when the visible light absorbing layer is an antimony-doped tin oxide film, it is preferable that the antimony-doped tin oxide film is formed by two or more coaters. In this case, when the impurity concentration distribution in the thickness direction of the antimony-doped tin oxide film is measured by X-ray photoelectron spectroscopy in the film-attached substrate, two or more peaks at which the impurity concentration is maximum are confirmed.

[0038] In the present invention, the thickness of the visible light absorbing layer is preferably 100 to 900 nm. When the thickness of the visible light absorbing layer is 100 nm or more, the film-coated substrate can be given sufficient heat shielding properties, and the transmittance of the film-coated substrate can be easily adjusted to a predetermined value. In addition, since the crystal grains can be grown to a certain size in the visible light absorbing layer, when another functional layer is formed on the visible light absorbing layer by crystal growth, the crystal grain size in the other functional layer can be easily grown. When the thickness of the visible light absorbing layer is 900 nm or less, the film surface is easily kept flat, so that the film thickness deviation can be reduced and the occurrence of transmission unevenness can be further suppressed. The thickness of the visible light absorbing layer is more preferably 120 nm or more, further preferably 150 nm or more, particularly preferably 200 nm or more, and more preferably 600 nm or less, further preferably 450 nm or less, particularly preferably 300 nm or less.

[0039] The thickness of the visible light absorbing layer may be adjusted depending on the desired transmittance of the film-coated substrate and the type and content of the impurity element doped into the doped metal oxide.

[0040] The thickness of the visible light absorbing layer can be measured by, for example, analysis in the depth direction using X-ray photoelectron spectroscopy. In addition, since the visible light absorbing layer is formed by crystal grains of metal oxide, the surface opposite to the main material has an uneven shape. Therefore, the "thickness" of the visible light absorbing layer varies depending on the location, but in the present invention, it represents the average thickness of the visible light absorbing layer in the measurement area.

[0041] The film of the film-coated substrate of the present invention may have other functional layers in addition to the visible light absorbing layer. Examples of the other functional layers include an infrared reflective layer 5 and an optical adjustment layer 7, as shown in FIG.

[0042] <Infrared reflective layer> The infrared reflective layer 5 is a layer that reflects infrared rays and provides heat insulation to the film-coated substrate, and has crystallinity. When the film-coated substrate 20 includes an infrared reflective layer, the film-coated substrate 20 includes a visible light absorbing layer 3 and an infrared reflective layer 5 from the side closer to the main material 1.

[0043] Examples of materials for forming the infrared reflective layer include doped metal oxides in which at least one metal oxide selected from the group consisting of tin oxide, indium oxide, zinc oxide, titanium oxide, tantalum oxide, and niobium oxide is doped with other elements (impurity elements). Examples of impurity elements to be doped include fluorine, antimony, tin, potassium, aluminum, tantalum, niobium, nitrogen, boron, indium, and carbon.

[0044] Specific examples of doped metal oxides include fluorine-doped tin oxide (FTO, a metal oxide in which F is added to SnO2), antimony-doped tin oxide (ATO, a metal oxide in which Sb is added to SnO2), tin-doped indium oxide (ITO, a metal oxide in which Sn is added to In2O3), gallium-doped zinc oxide (GZO, a metal oxide in which Ga is added to ZnO), aluminum-doped zinc oxide (AZO, a metal oxide in which Al is added to ZnO), tantalum-doped tin oxide (a metal oxide in which Ta is added to SnO2), niobium-doped tin oxide (a metal oxide in which Nb is added to SnO2), tantalum-doped titanium oxide (a metal oxide in which Ta is added to Ti), niobium-doped titanium oxide (a metal oxide in which Nb is added to Ti), aluminum-doped tin oxide (a metal oxide in which Al is added to SnO2), fluorine-doped titanium oxide (a metal oxide in which F is added to Ti), and nitrogen-doped titanium oxide (a metal oxide in which N is added to Ti).

[0045] In particular, the infrared reflective layer preferably comprises a film made of a doped metal oxide in which at least one metal oxide selected from the group consisting of tin oxide, indium oxide, and zinc oxide is doped with another element, and the other element is preferably at least one selected from the group consisting of fluorine, antimony, tin, gallium, and aluminum. Specifically, it is more preferable that the infrared reflective layer comprises a film of at least one doped metal oxide selected from the group consisting of fluorine-doped tin oxide (FTO), antimony-doped tin oxide (ATO), tin-doped indium oxide (ITO), gallium-doped zinc oxide (GZO) and aluminum-doped zinc oxide (AZO), and from the viewpoint of obtaining higher thermal insulation, it is even more preferable that the infrared reflective layer comprises a fluorine-doped tin oxide (FTO) film.

[0046] The infrared reflective layer may be made of a single film layer, or may be made of two or more films made of different materials or containing different elements.

[0047] The content of the impurity element contained in the infrared reflective layer may be appropriately set depending on the impurity element to be doped, but the concentration is preferably 0.01 to 20 mol%. When the concentration of the impurity element contained in the infrared reflective layer is 0.01 mol% or more, the heat insulating effect can be exhibited and the transmittance of the film-coated substrate can be easily adjusted to a predetermined value, and when it is 20 mol% or less, good crystallinity can be maintained. The concentration of impurity elements contained in the infrared reflective layer is preferably 0.01 mol% or more, more preferably 0.1 mol% or more, even more preferably 0.5 mol% or more, and more preferably 10 mol% or less, even more preferably 8 mol% or less, and particularly preferably 5 mol% or less. When the infrared reflective layer contains a plurality of impurity elements, the concentration of the impurity element refers to the total amount thereof.

[0048] The composition of the infrared reflective layer and the concentration of impurity elements can be identified by X-ray photoelectron spectroscopy (XPS) or secondary ion mass spectrometry (SIMS) as described above.

[0049] In the present invention, the thickness of the infrared reflective layer is preferably 100 to 400 nm. When the thickness of the infrared reflective layer is 100 nm or more, the heat insulating performance of the film-coated substrate is improved, and the transmittance of the film-coated substrate is easily adjusted to a predetermined value. When the thickness of the infrared reflective layer is 400 nm or less, the surface can be made flat. The thickness of the infrared reflective layer is more preferably 120 nm or more, further preferably 130 nm or more, particularly preferably 150 nm or more, and is more preferably 380 nm or less, further preferably 350 nm or less.

[0050] The thickness of the infrared reflective layer can be measured by depth direction analysis using X-ray photoelectron spectroscopy. When the infrared reflective layer is composed of multiple layers of different materials, the "thickness" of the infrared reflective layer is represented by the sum of the thicknesses of the individual layers. The infrared reflective layer is formed by crystal grains of a metal oxide, and the surface of the visible light absorbing layer on which the infrared reflective layer is laminated is uneven, so that the surface of the layer (i.e., the surface on the visible light absorbing layer side and the surface opposite the visible light absorbing layer) has an uneven shape. Therefore, the "thickness" of the infrared reflective layer varies depending on the location, but in the present invention, it represents the average thickness of the infrared reflective layer in the measurement area.

[0051] When the film-coated substrate has an infrared reflective layer, the visible light absorbing layer and the infrared reflective layer may be formed using films of the same composition, but by changing the film thickness, concentration, etc. depending on the function, it is possible to give the film characteristics according to the required function.

[0052] It is preferable that the visible light absorbing layer and the infrared reflective layer are formed containing the same type of metal oxide. If the metal oxide contained in the visible light absorbing layer and the metal oxide contained in the infrared reflective layer are the same type, the crystal grains do not stop growing when the infrared reflective layer is formed, and the crystal grains in the infrared reflective layer can be grown large. For example, when the metal oxide constituting the visible light absorbing layer is tin oxide, the infrared reflective layer is preferably a doped tin oxide film. Specifically, it is preferable that the visible light absorbing layer is made of an antimony-doped tin oxide (ATO) film, and the infrared reflective layer is made of a fluorine-doped tin oxide (FTO) film.

[0053] When the infrared reflective layer contains fluorine-doped tin oxide (FTO), the fluorine concentration in the infrared reflective layer is preferably 0.01 mol% or more, more preferably 0.05 mol% or more, and even more preferably 0.1 mol% or more. From the viewpoint of suppressing the inclusion of inactive fluorine and reducing fluorine scattering to increase the mobility, the fluorine concentration is preferably 10 mol% or less, more preferably 5 mol% or less, and even more preferably 3 mol% or less.

[0054] <Optical adjustment layer> The optical adjustment layer 7 is a layer that adjusts the reflected color and transmitted color to a predetermined color. When the film-coated substrate 20 includes the optical adjustment layer 7, the optical adjustment layer 7 is preferably disposed between the main material 1 and the visible light absorbing layer 3, as shown in FIG.

[0055] Examples of materials constituting the optical adjustment layer include silicon oxide carbide (SiOC), silicon oxide (SiO2), titanium oxide (TiO2), tin oxide (SnO2), silicon oxide nitride (SiON), etc. The optical adjustment layer may be made of one layer, or may be made of two or more layers. It may also be a mixture of two or more of the above materials.

[0056] Specifically, examples of the optical adjustment layer include a SiOC film, a SiOC / SiO2 laminated film in which a SiOC film and a SiO2 film are laminated in this order from the main material side, a TiO2 / SiO2 laminated film in which a TiO2 film and a SiO2 film are laminated in this order from the main material side, and a SnO2 / SiO2 laminated film in which a SnO2 film and a SiO2 film are laminated in this order from the main material side. In particular, from the viewpoint of alkali barrier properties, it is preferable that the optical adjustment layer contains silicon, and it is more preferable that it has at least one film selected from the group consisting of a SiOC film, a SiOC / SiO2 laminate film, a TiO2 / SiO2 laminate film, and a SnO2 / SiO2 laminate film, and it is even more preferable that it has a SiOC film.

[0057] The amount of silicon contained in the entire optical adjustment layer is preferably in the range of 5 to 40 mol %, and more preferably 10 to 33 mol %.

[0058] The thickness of the optical adjustment layer is preferably 10 to 100 nm. When the thickness of the optical adjustment layer is 10 nm or more, the surface of the main material can be uniformly covered, and when the thickness is 100 nm or less, the occurrence of new optical interference in the optical adjustment layer is suppressed, and the optical adjustment layer can exert the desired effect. The thickness of the optical adjustment layer is more preferably 20 nm or more, further preferably 25 nm or more, particularly preferably 30 nm or more, and is preferably 100 nm or less, more preferably 90 nm or less, further preferably 80 nm or less, particularly preferably 70 nm or less.

[0059] When the optical adjustment layer is composed of multiple layers of different materials, the "thickness" of the optical adjustment layer is represented by the sum of the thicknesses of the individual layers.

[0060] <Other layers> The film-coated substrate of the present invention may have other layers as long as the effects of the present invention are not impaired. The other layers include an overcoat layer.

[0061] In the case where the film of the film-attached substrate of the present invention has a functional layer other than the visible light absorbing layer, the total thickness of the film is preferably 500 to 1600 nm. When the film thickness is 500 nm or more, the function of each layer is fully exerted, and the transmittance is easily adjusted. Also, when the film thickness is 1600 nm or less, the thickness of the film-attached substrate does not become too thick.

[0062] (Physical properties of film-coated substrate) The film-attached substrate of the present invention preferably has an arithmetic mean roughness Ra of the substrate surface (surface on the film side) of 40 nm or less. When the arithmetic mean roughness Ra of the substrate surface is 40 nm or less, the effects of the present invention are easily obtained. The arithmetic mean roughness Ra of the substrate surface is more preferably 30 nm or less, and even more preferably 20 nm or less, and from the viewpoint of antiglare properties, is preferably 1 nm or more, more preferably 3 nm or more, and even more preferably 5 nm or more.

[0063] The arithmetic mean roughness Ra of the surface of the film-coated substrate can be measured by a known method using, for example, an atomic force microscope (AFM), a confocal optical laser microscope, a contact-type surface roughness meter, or the like.

[0064] The film-coated substrate of the present invention has a visible light transmittance (T vaA light source transmittance (T va ) is less than 30%, sufficient heat ray absorption can be ensured and the film-coated substrate has suitable visible light absorption. A light source transmittance (T va ) is more preferably 28% or less, even more preferably 25% or less, and particularly preferably 20% or less. In addition, from the viewpoint of being able to achieve a desirable appearance when used in automobiles and buildings, the A light source transmittance (T va ) is preferably 1% or more, more preferably 2% or more, and even more preferably 4% or more.

[0065] In addition, the solar transmittance of the film-coated substrate (T e ) is preferably less than 30%. e ) is less than 30%, sufficient heat ray absorption can be ensured and the film-coated substrate has suitable visible light absorption. Solar transmittance (T e ) is more preferably 28% or less, further preferably 25% or less, and particularly preferably 20% or less. From the viewpoint of being able to give a desirable appearance when used in automobiles or buildings, the solar transmittance (T e ) is preferably 1% or more, more preferably 2% or more, and even more preferably 4% or more.

[0066] A light source transmittance (T va ) and solar transmittance (T e ) can be measured using a commercially available spectrophotometer (for example, "Lambda 1050" manufactured by PerkinElmer, etc.).

[0067] The A light source transmittance and solar radiation transmittance can be adjusted to desired transmittances by adjusting the impurity concentration in the film and the thickness of each layer constituting the film.

[0068] In addition, the emissivity of the film-coated substrate (E n It is preferable that the emissivity (E n ) less than 0.25, excellent heat insulation properties can be obtained. Emissivity (E n ) is more preferably 0.23 or less, and even more preferably 0.20 or less. The lower limit of the emissivity is not particularly limited because the lower the emissivity, the better the heat insulating property, but it is preferably 0.01 or more, more preferably 0.02 or more, and even more preferably 0.04 or more.

[0069] Emissivity is the ratio of the light energy emitted by an object through thermal radiation (radiance) to the light energy emitted by a black body at the same temperature (blackbody radiation), taken as 1. The emissivity of a film-coated substrate can be measured on the film side surface using a commercially available emissometer (for example, the "Emissometer model AE1" manufactured by Devices & Services) according to the method described in JIS R3106 (2019).

[0070] The emissivity can be adjusted to a desired value by adjusting the film thickness, carrier density, mobility, sheet resistance, etc. of the infrared reflective layer.

[0071] The sheet resistance of the film-coated substrate is preferably 30 Ω / □ (ohm / square) or less. Emissivity and sheet resistance are correlated, and if the sheet resistance is 30 Ω / □ or less, electricity flows easily, resulting in low emissivity and excellent thermal insulation. The sheet resistance value is more preferably 25 Ω / □ or less, and even more preferably 20 Ω / □ or less. In addition, since the lower the sheet resistance value, the easier it is for electricity to flow and the lower the emissivity, the lower limit of the sheet resistance value is not particularly limited, but it is preferably 1 Ω / □ or more, more preferably 2 Ω / □ or more, and even more preferably 3 Ω / □ or more.

[0072] The value of the sheet resistance can be measured by Hall effect measurement.

[0073] The film-coated substrate of the present invention has an L * a * b * Color coordinate a of the reflected color in the color system * is preferably 5 to -20, *It is preferable that L is 10 to -20. * a * b * In the color system, color and saturation are expressed as a * and b * and a * is large (+a * ) and red direction, a * is small (-a * ) and green direction, and b * is large (+b * ) and yellow direction, b * is small (-b * ) and indicates the blue direction.

[0074] a * The value is preferably -15 or more, more preferably -12 or more, and more preferably 2 or less, and even more preferably 0 or less. * The value is more preferably -15 or greater, even more preferably -10 or greater, and is more preferably 5 or less, even more preferably 2 or less.

[0075] In addition, the film-coated substrate of the present invention has an L * a * b * Color coordinate L of reflected color in color system * It is preferable that L is 42 or less. * represents lightness, and L * A value of 42 or less reduces the intensity of reflected light and reduces undesirable glare. * The value is more preferably 40 or less, and even more preferably 35 or less. There is no particular lower limit, but considering the reflectance of a general infrared reflective layer, L * A value of 20 or greater is preferred, 25 or greater is more preferred, and 30 or greater is particularly preferred.

[0076] a * Value, b * Value and L * The value can be measured using an ultraviolet-visible spectrophotometer or a colorimeter, and the value is measured when irradiated with light from a D65 light source at an incident angle of 10 degrees using these measuring instruments.

[0077] In the present invention, * Value, b * Value and L * The value can be adjusted to a desired value by adjusting the impurity concentration in the film and the thickness of each layer constituting the film.

[0078] The mobility of the membrane on the membrane substrate is 20 cm 2 / Vs or more. The higher the mobility, the better the electrical conductivity, resulting in improved thermal insulation. 2 When the dielectric constant is 0.1 V or more, excellent heat insulation can be obtained. The membrane mobility is 25 cm 2 / Vs or more is preferable, and 27cm 2 / Vs or more is more preferable, 30cm 2 / Vs or more is particularly preferable, 35cm 2 / Vs or more is most preferable. The higher the mobility, the better, so there is no particular upper limit, but it is preferably 100 cm 2 / Vs or less, and 90cm 2 / Vs or less is preferable, 80cm 2 / Vs or less is more preferable.

[0079] The mobility of the film-coated substrate can be measured by Hall effect measurement.

[0080] The carrier density of the film-coated substrate is 1×10 19 / cm 3 The carrier density is the number of free electrons or holes per unit volume in a substance. 19 / cm 3 If the thickness is more than this, excellent heat insulation properties can be obtained. The carrier density of the film-coated substrate is 2×10 19 / cm 3 More preferably, 5×10 19 / cm 3 More preferably, 1×10 20 / cm 3The higher the carrier density, the better, so there is no particular upper limit to the carrier density. 22 / cm 3 Preferably, it is less than or equal to 1×10 21 / cm 3 Less than 5×10 is preferable. 20 / cm 3 The following is even more preferred:

[0081] The carrier density of the film-coated substrate can be measured by Hall effect measurement.

[0082] The film-coated substrate preferably has a haze of 10% or less. When the haze is 10% or less, the film-coated substrate is prevented from becoming turbid, and a film-coated substrate with excellent appearance can be obtained. The haze is more preferably 9% or less, further preferably 7% or less, and particularly preferably 5% or less. Since the smaller the haze, the better, the lower limit is not particularly limited.

[0083] Haze can be measured using a commercially available measuring device (for example, a haze meter "HZ-V3" manufactured by Suga Test Instruments Co., Ltd.) or by the method described in JIS K 7136:2000.

[0084] (Method of manufacturing film-coated substrate) A method for producing a film-coated substrate according to an embodiment of the present invention (hereinafter, also referred to as the present production method) will be described. The present production method includes forming a film on a main material. In the present production method, the main material is glass, and the film formation includes forming a visible light absorbing layer made of a doped metal oxide doped with an impurity element by a thermal CVD method on the glass production line, and the visible light absorbing layer is formed using two or more coaters. In this specification, the method for forming a film by a thermal CVD method on a glass production line may be referred to as an online CVD method. An example of the present production method will be described below.

[0085] The method for producing a film-coated substrate according to an embodiment of the present invention includes forming a visible light absorbing layer by an online CVD method, and two or more coaters are used when forming the visible light absorbing layer. This can suppress the unevenness in the transmission of the obtained film-coated substrate. The reason for this is that, even if a layer with a relatively low visible light transmittance is formed using two or more coaters, and unevenness in the film thickness and the resulting unevenness in the transmission occur, the unevenness is homogenized due to the different patterns of unevenness caused by each coater, and as a result, the unevenness in the film thickness of the obtained visible light absorbing layer is reduced.

[0086] When the film is formed by thermal CVD on a glass production line, the main material of the film-coated substrate is glass. Specific preferred embodiments of the glass are as described above, and may be, for example, soda-lime silicate-based highly transparent glass.

[0087] By forming the visible light absorbing layer by the thermal CVD method, Sb replaces the Sn site, and it becomes a high-temperature process suitable for obtaining a film incorporated into the crystal structure. This makes it possible to form a film with excellent heat ray absorption properties. Furthermore, if it can be formed by the atmospheric pressure CVD method, a large-scale vacuum device is not required, further increasing productivity. And the online CVD method is preferable because it has superior manufacturing efficiency compared to the offline CVD method, in which the film is formed by reheating the glass substrate manufactured by the float method.

[0088] In the online CVD method, a glass production line in which a film is formed on the glass production line by the thermal CVD method is, for example, a production line in which glass is produced by the float method. A glass production apparatus in the float method includes, for example, a melting furnace for melting glass raw materials, a float bath for floating molten glass on molten metal to form a glass ribbon, and an annealing furnace for annealing the glass ribbon. The film is formed on the glass ribbon by the thermal CVD method, for example, in a float bath or an annealing furnace. In the float bath, there may be restrictions on the oxide film formation conditions in order to suppress oxidation of the molten metal, so it is preferable to form the film in an annealing furnace, especially when forming an oxide film.

[0089] FIG. 4 is a diagram showing a schematic view of an example of a glass manufacturing apparatus used in the present manufacturing method, and is a diagram partially showing the float bath 52 and the annealing furnace 54 of the glass manufacturing apparatus. In FIG. 4, the glass ribbon 70 is transported in the direction of the arrow in the figure, that is, from the float bath 52 side to the annealing furnace 54 side. A sealing gate (not shown) for preventing heat radiation from the float bath may be provided in the boundary area between the float bath 52 and the annealing furnace 54. The annealing furnace 54 supplies a heat amount with its output controlled by, for example, a combustion gas or an electric heater to a necessary position in the furnace, and slowly cools the glass ribbon transported by the transport rollers 55 to a temperature range close to room temperature, thereby eliminating residual stress inherent in the glass ribbon and suppressing the occurrence of warping or cracking in the glass ribbon. A plurality of coaters 60 (60a to 60c) are provided in the annealing furnace 54, and a film (laminated film) is formed on the glass ribbon by a CVD method. Incidentally, the temperature of the glass ribbon when it enters the annealing furnace 54 is often around 610° C. (Tg+50° C.) in the case of soda-lime silicate glass.

[0090] In FIG. 4, three coaters 60a to 60c are shown, and a laminated film is formed on the conveyed glass ribbon. For example, an electric heater (not shown) may be provided between each coater. The number of coaters 60 is not limited to the above, and can be appropriately adjusted according to the number of layers of the laminated film and the number of coaters used to form the visible light absorbing layer. The number of electric heaters can also be increased or decreased as necessary. The electric heater prevents the temperature of the glass ribbon from decreasing too much from the entrance to the exit of the annealing furnace. On the other hand, the heater installed between the coaters can heat the glass ribbon between the coaters, but cannot heat the glass ribbon below the coater. The installation of this heater does not affect the temperature change of the glass ribbon cooled from the entrance to the exit of the coater.

[0091] 5 is a diagram showing a schematic configuration example of a coater in a glass manufacturing apparatus. The coater 60 is disposed above the glass ribbon 70, on the opposite side of the conveying roller 55 with the glass ribbon 70 therebetween. Each coater has an elongated slit-shaped air outlet 61 provided at approximately the center of a lower surface 65 in a direction perpendicular to the conveying direction of the glass ribbon, and exhaust ports 62 extending parallel to the air outlet 61 are provided on both sides of the air outlet 61 in the front-rear direction.

[0092] In the blowing port 61, a first orifice 61a located in the center, and second and third orifices 61b and 61c, which are located in the front-rear direction on either side of the first orifice 61a and are configured such that the flow paths are inclined from the source gas supply source toward the first orifice 61a, are opened. The width of the blowing port 61 and the exhaust port 62 is set to be equal to or larger than the width of the glass ribbon 70. Moreover, reference numerals 66a and 66b denote cooling ducts, which circulate a cooling medium such as a cooling gas or oil to keep the coater 60 at an optimum temperature, for example, 100 to 220°C (measured on the lower surface of the coater). The lower surface of the coater 60 is the surface that comes into contact with the source gas, and if the temperature is too high, the source gas that comes into contact with the lower surface of the coater 60 reacts with heat and adheres to the lower surface, forming an unnecessary film. For this reason, the upper limit is preferably 250°C or less. Moreover, if the temperature is too low, the amount of heat exchange with the glass ribbon increases, causing a sudden drop in temperature of the glass ribbon. For this reason, the lower limit is preferably 100°C or more.

[0093] The coater 60 is disposed above the glass ribbon 70 with a gap of 3 mm to 30 mm. Therefore, the lower surface 65 of the coater 60 is disposed opposite the glass ribbon 70 conveyed in the annealing furnace 54 with a gap of 3 mm to 30 mm therebetween. The smaller the gap, the more advantageous it is for the film thickness, film quality, and film formation speed during film formation. However, if the gap fluctuates due to warping or vibration of the glass ribbon, the effect on the film thickness and film quality becomes large. In addition, if the gap is large, the efficiency of the raw material during film formation decreases. In consideration of the film thickness, film quality, and film formation speed, the gap is preferably 4 to 12 mm, more preferably 5 to 10 mm.

[0094] For example, the first orifice 61a blows out a gas containing a main raw material of a compound for forming an oxide film. The second and third orifices 61b and 61c blow out a reactive gas (a gas that serves as an oxygen source) for forming an oxide film. In this way, the raw material gases may be supplied from a plurality of orifices and mixed on the surface of the surface on which the film is to be formed, or the raw material gases may be mixed in advance and then supplied. The exhaust port 62 exhausts excess gas after the CVD reaction. The specific configuration of the coater is not limited to the above, and may be appropriately changed within a range in which the effects of the present invention can be obtained.

[0095] For example, in the case of forming an antimony-doped tin oxide film as a visible light absorbing layer and a fluorine-doped tin oxide film as an infrared reflective layer on a main material in the apparatus configuration of FIG. 4, the antimony-doped tin oxide film is formed by the coater 60a, and further, the coater 60b forms an antimony-doped tin oxide film on the antimony-doped tin oxide film formed by the coater 60a. In this way, the visible light absorbing layer (antimony-doped tin oxide film) is formed by using two coaters. Then, the infrared reflective layer is formed on the visible light absorbing layer by the coater 60c. Two or more coaters may be used to form the visible light absorbing layer, and the number of coaters may be three or more. From the viewpoint of the thermal state (temperature retention) of the glass ribbon, the number of coaters used to form the visible light absorbing layer is preferably, for example, 2 to 4.

[0096] The coater can be classified into a turbulent coater and a laminar coater depending on the flow of gas blown out from the blowing port 61. Either coater can be used for film formation by the present manufacturing method. In addition, as the two or more coaters used for film formation of the visible light absorbing layer, a turbulent coater and a laminar coater may be combined, or multiple combinations of either only turbulent coaters or only laminar coaters may be used.

[0097] The preferred film thickness of the visible light absorbing layer is as described above, but for example, when the visible light absorbing layer is formed by the two coaters 60a and 60b, the ratio of the film thickness of the portion formed by the coater 60a to the film thickness of the portion formed by the coater 60b is not particularly limited. For example, it may be 1:5 to 5:1, 1:3 to 3:1, or 1:2 to 2:1.

[0098] Furthermore, if the film-coated substrate further includes an optical adjustment layer, a further coater 60d may be added before coater 60a to deposit the optical adjustment layer, the visible light absorption layer, and the infrared reflective layer in that order, or if each layer is composed of multiple layers, the number and arrangement of coaters may be adjusted accordingly.

[0099] Next, the method of forming each layer will be described in more detail. As described above, the visible light absorption layer can be constructed using various thin film materials, such as tin oxide, indium oxide, zinc oxide, antimony-doped tin oxide (ATO), fluorine-doped tin oxide (FTO), tin-doped indium oxide (ITO), gallium-doped zinc oxide (GZO), and aluminum-doped zinc oxide (AZO).

[0100] For example, a case will be described in which the infrared reflective layer is made of fluorine-doped tin oxide (FTO), the visible light absorbing layer is made of antimony-doped tin oxide (ATO), and each layer is formed by thermal CVD.

[0101] The visible light absorbing layer uses a mixture of an inorganic or organic tin compound and an antimony compound as a raw material. The amount of the antimony compound per 1 mol of the tin compound in the raw material gas is preferably 0.06 mol or more. This allows the formation of a high-concentration ATO.

[0102] Examples of tin compounds include monobutyltin trichloride (C4H9SnCl3) and tin tetrachloride (SnCl4). Organic tin compounds are particularly preferred. When inorganic tin compounds are used, the crystal grains tend to grow quickly and the surface tends to become very uneven.

[0103] Examples of antimony compounds include antimony trichloride (SbCl3) and antimony pentachloride (SbCl5). As the antimony compound, antimony trichloride is particularly preferable. For example, antimony trichloride reacts violently with water in the source gas to generate particle clusters of antimony trioxide (Sb2O3) and antimony pentoxide (Sb2O5) in the gas phase. Therefore, by including these particle clusters in the film, the degree of surface roughness can be controlled.

[0104] In forming the visible light absorbing layer, the source gas may be mixed in advance and then transported. Alternatively, the source gas may be mixed on the surface of the glass substrate on which the film is to be formed. When the source material is liquid, the source material may be vaporized into a gaseous state using a bubbling method or a vaporizer.

[0105] The amount of water per 1 mol of the tin compound in the raw material gas is preferably 5 to 50 mol. If the amount of water is less than 5 mol, the resistance value of the film formed is likely to increase, and as a result, the heat ray absorption function of antimony is likely to decrease. In addition, the number of starting points of nucleation is reduced, and as a result, crystal grains are likely to grow large, and the surface is likely to become uneven. Furthermore, the film formation rate is reduced, and there is a risk of productivity decreasing. In addition, it is known that the reaction of antimony trichloride also proceeds by hydrolysis, and if the water ratio is too low, antimony cannot be added efficiently, and a visible light absorption layer with a high antimony concentration cannot be obtained. The amount of water per mol of antimony compound in the raw material gas is preferably 30 mol or more. On the other hand, if the amount of water exceeds 50 mol, the raw material gas volume increases with the increase in the amount of water, and the flow rate of the raw material gas increases, which may decrease the film deposition efficiency. In addition, the number of starting points of nucleation is increased, and as a result, crystal grains are likely to grow small, and the surface is likely to become flat.

[0106] When the raw material gas contains oxygen, the amount of oxygen per 1 mol of the tin compound in the raw material gas is preferably more than 0 mol and not more than 40 mol, more preferably 4 to 40 mol. If the amount of oxygen is too small, the resistance value of the film formed may increase, so it is more preferably 4 mol or more. On the other hand, if the amount of oxygen exceeds 40 mol, the raw material gas volume increases, and the flow rate of the raw material gas increases, which may reduce the film deposition efficiency.

[0107] The temperature of the main material (glass substrate) when forming the visible light absorbing layer is preferably 500 to 650°C. If the temperature of the glass is less than 500°C, the formation rate of the visible light absorbing layer may decrease. In addition, the precursor generated by decomposition of the raw material gas diffuses on the surface of the glass and the visible light absorbing layer at a higher rate than the reaction rate on the surface of the glass and the visible light absorbing layer. As a result, more precursor flows into the unevenness of the surface of the glass and the visible light absorbing layer, and the surface tends to become flat. On the other hand, if the temperature of the glass is more than 650°C, the film is formed in a state where the viscosity of the glass is low, so warping may occur in the process of lowering the temperature of the glass to room temperature. In addition, the precursor reacts on the surface of the glass and the visible light absorbing layer at a higher rate than the diffusion rate on the surface of the glass and the visible light absorbing layer. As a result, the precursor does not flow into the unevenness of the surface of the glass and the visible light absorbing layer very much, and the unevenness of the surface tends to become large.

[0108] The thickness of the visible light absorbing layer and the content of impurity elements can be controlled by the type of raw material, the raw material gas concentration, the flow rate of the raw material gas blown onto the layer on which the visible light absorbing layer is to be formed, the processing temperature, the reaction gas residence time derived from the coating beam structure, and the like.

[0109] In the present invention, when the film-coated substrate has an infrared reflective layer, the infrared reflective layer is formed on the visible light absorbing layer.

[0110] As described above, the infrared reflective layer can be constructed using various thin film materials, such as fluorine-doped tin oxide (FTO), antimony-doped tin oxide (ATO), tin-doped indium oxide (ITO), gallium-doped zinc oxide (GZO), and aluminum-doped zinc oxide (AZO).

[0111] When the infrared reflective layer is made of, for example, fluorine-doped tin oxide (FTO) or antimony-doped tin oxide (ATO), the surface irregularities of the infrared reflective layer can be increased, making it easy to adjust the color tone to a predetermined range.

[0112] When the infrared reflective layer is made of, for example, aluminum-doped zinc oxide (AZO) or gallium-doped zinc oxide (GZO), the crystal orientation tends to be uniform and the surface tends to be flat.

[0113] In addition, tin-doped indium oxide (ITO) has a strong infrared reflecting function and is often used in a film thickness range of about 100 nm. Therefore, when the infrared reflecting layer is made of tin-doped indium oxide (ITO), it may be difficult to adjust the color tone of the reflected color to a specified range, and the crystal grain growth may be insufficient, leading to a flat surface.

[0114] For example, when the infrared reflective layer is made of a fluorine-doped tin oxide (FTO) layer and is formed by thermal CVD, a mixture of an inorganic or organic tin compound and a fluorine compound is used as a raw material.

[0115] As mentioned above, examples of the tin compound include monobutyltin trichloride (C4H9SnCl3) and tin tetrachloride (SnCl4). As the tin compound, organic tin compounds are particularly preferred. When an inorganic tin compound is used as the tin compound, the crystal grains tend to grow quickly and the surface tends to become very uneven.

[0116] The fluorine compounds include hydrogen fluoride and trifluoroacetic acid.

[0117] In forming the infrared reflective layer, the raw material gas may be mixed in advance and then transported. Alternatively, the raw material gas may be mixed on the surface of the object to be formed (specifically, the visible light absorbing layer). When the raw material is liquid, the raw material may be vaporized into a gaseous state using a bubbling method or a vaporizer.

[0118] The amount of water per 1 mol of the tin compound in the raw material gas is preferably 5 to 50 mol. If the amount of water is less than 5 mol, the resistance of the film formed is likely to increase, and as a result, the infrared reflection function is likely to decrease. In addition, the number of starting points for nucleation is reduced, and as a result, the crystal grains tend to grow large, and the surface is likely to become very uneven. On the other hand, if the amount of water is more than 50 mol, the increase in the amount of water increases the volume of the raw material gas, and the flow rate of the raw material gas increases, which may decrease the film deposition efficiency. In addition, the number of starting points for nucleation is increased, and as a result, the crystal grains tend to grow small, and the surface is likely to become flat.

[0119] When the raw material gas contains oxygen, the amount of oxygen per 1 mol of the tin compound in the raw material gas is preferably more than 0 mol and not more than 40 mol, more preferably 4 to 40 mol. If the amount of oxygen is less than 4 mol, the resistance value of the film formed may increase. On the other hand, if the amount of oxygen is more than 40 mol, the raw material gas volume increases, and the flow rate of the raw material gas increases, which may decrease the film deposition efficiency.

[0120] In forming the infrared reflective layer, the amount of the fluorine compound per 1 mol of the tin compound in the raw material gas is preferably 0.1 to 1.2 mol. If the amount of the fluorine compound is less than 0.1 mol or more than 1.2 mol, the resistance value of the formed film is likely to increase.

[0121] The temperature at which the infrared reflective layer is formed is preferably 500 to 650°C. If the treatment temperature is less than 500°C, the formation rate of the infrared reflective layer may decrease. In addition, the precursor generated by decomposition of the raw material gas diffuses on the surface of the glass and the infrared reflective layer at a higher rate than the reaction rate on the surface of the glass and the infrared reflective layer. As a result, more precursor flows into the unevenness of the surface of the glass and the infrared reflective layer, and the surface tends to become flat. On the other hand, if the treatment temperature is more than 650°C, the film is formed in a state where the viscosity of the glass is low, so that warping may occur in the process of cooling the glass to room temperature. In addition, the precursor reacts on the surface of the glass and the infrared reflective layer at a higher rate than the diffusion rate on the surface of the glass and the infrared reflective layer. As a result, the precursor does not flow into the unevenness of the surface of the glass and the infrared reflective layer very much, and the unevenness of the surface tends to increase.

[0122] The thickness of the infrared reflective layer and the content of impurity elements can be controlled by the type of raw material, the raw material gas concentration, the flow rate of the raw material gas sprayed onto the layer forming the visible light absorbing layer, the processing temperature, the reaction gas residence time derived from the coating beam structure, etc.

[0123] When the film-coated substrate further includes an optical adjustment layer, the optical adjustment layer can be formed using various thin film materials such as SiOC, SiO2, TiO2, and SnO2, as described above. The optical adjustment layer may be made of one layer, or may be a laminate of two or more layers.

[0124] For example, when the optical adjustment layer includes a silicon oxide carbide (SiOC) layer, the optical adjustment layer may be formed by a thermal CVD method. In this case, the raw material may be, for example, a mixed gas containing monosilane (SiH4), ethylene, and carbon dioxide. When such a carbon-containing gas is used, particulate silicon compounds are easily formed together with film-like silicon compounds, and the haze ratio can be increased. The source gases may be mixed in advance and then transported onto the first surface of the glass substrate, or the source gases may be mixed on the first surface of the glass substrate.

[0125] Furthermore, for example, when the optical adjustment layer includes a silicon oxide (SiO2) layer, the raw material may be, for example, a mixed gas of monosilane (SiH4), tetraethoxysilane, oxygen, and the like.

[0126] Furthermore, for example, when the optical adjustment layer includes a titanium oxide (TiO2) layer, examples of the raw material include tetraisopropyl orthotitanate (TTIP), titanium tetrachloride, etc. Among them, tetraisopropyl orthotitanate (TTIP) is more preferable.

[0127] The temperature of the glass substrate when the optical adjustment layer is formed is preferably 500 to 900° C. If the temperature of the glass substrate is less than 500° C. or more than 900° C., the film formation speed tends to decrease.

[0128] For example, SiO x C y A layer consisting of (hereinafter, SiO x C y This section describes a method for forming a thin film of the SiO 2 (also called a SiO 2 layer) by CVD. In the CVD method, for example, a glass substrate heated to a temperature of 500 to 800° C. is reacted with a gaseous source to deposit SiO x C y It is preferred to form a layer. From the viewpoint of improving the reaction rate of the CVD method, the temperature of the glass substrate is preferably 500° C. or higher, more preferably 600° C. or higher, and even more preferably 700° C. or higher. Moreover, from the viewpoint of glass softening, the temperature of the glass substrate is more preferably 800° C. or lower, and even more preferably 760° C. or lower.

[0129] The gaseous feedstock preferably comprises a silicon-containing material, an oxidant, and an unsaturated hydrocarbon.

[0130] Examples of silicon-containing substances include silanes such as monosilane (SiH4), disilane (Si2H6), dichlorosilane (SiH2Cl2), and silane trioxide (SiHCl3), alkylated silanes such as tetramethylsilane ((CH3)4Si), silicon tetrafluoride (SiF4), and silicon tetrachloride (SiCl4), with silanes being preferred and monosilane being more preferred.

[0131] The oxidizing agent includes compounds containing oxygen such as carbon dioxide (CO2), carbon monoxide (CO), oxygen (O2), and water vapor (H2O), with carbon dioxide being preferred.

[0132] Examples of unsaturated hydrocarbons include ethylenically unsaturated hydrocarbons (olefins), acetylenically unsaturated hydrocarbons, aromatic compounds, etc., and compounds that are gaseous at normal temperature and pressure are preferred. As the unsaturated hydrocarbon, olefins are preferred, olefins having 2 to 4 carbon atoms are more preferred, and ethylene is even more preferred.

[0133] By adjusting the mixture ratio of gaseous materials, SiO x C y SiO in the layer x C y The composition can be adjusted. Specifically, the volume ratio of the oxidizing agent to the silicon-containing substance is preferably 8.5 or more, more preferably 12 or more, and even more preferably 20 or more. In addition, the volume ratio of the oxidizing agent to the silicon-containing substance is preferably 50 or less.

[0134] The volume ratio of the unsaturated hydrocarbon to the silicon-containing substance is preferably 0.5 or more, more preferably 1.0 or more, and the volume ratio of the unsaturated hydrocarbon to the silicon-containing substance is preferably 3.5 or less, more preferably 2.7 or less.

[0135] SiO x C y The composition of SiO changes due to the interaction between the oxidizing agent and the unsaturated hydrocarbon. x C yIn order to adjust the composition to the preferred range, the combination of the volume ratio of the oxidizing agent and the volume ratio of the unsaturated hydrocarbon to the silicon-containing substance is important, and it is preferable to adjust both of them to be within the above-mentioned preferred range.

[0136] SiO x C y The layer thickness can be controlled by the type of raw material, raw material gas concentration, flow rate of the raw material gas sprayed onto the glass ribbon or glass substrate, substrate temperature, reactive gas residence time derived from the coating beam structure, and the like.

[0137] In the present invention, when an overcoat layer is provided, the overcoat layer is disposed on the surface of the infrared reflective layer after the infrared reflective layer is formed.

[0138] The overcoat layer is formed, for example, by a wet method.

[0139] In this case, first, a coating solution for the overcoat layer is prepared. The coating solution includes a metal oxide precursor, an organic solvent, and water. Particles and / or solids may also be added to the coating solution. The composition of the particles may be the same as or different from the metal oxide precursor.

[0140] The coating solution is then applied onto the infrared reflective layer of the filmed substrate. The coating method is not particularly limited, and a general method such as spin coating may be used.

[0141] Next, the substrate with the film on which the coating solution is applied is heat-treated in the atmosphere. The temperature of the heat treatment is, for example, in the range of 80 to 650° C. The heating time is, for example, in the range of 5 minutes to 360 minutes.

[0142] The heat treatment may be carried out using a common device such as a hot air circulating oven or an IR heater oven, etc. Also, an overcoat layer may be formed from the coating solution by a UV curing process, a microwave process, etc.

[0143] This allows the overcoat layer to be formed on the infrared reflective layer.

[0144] The heat treatment does not necessarily have to be carried out at this stage, that is, the coating solution may be heated by utilizing a heating step carried out at another stage.

[0145] By such a process, the film-attached substrate according to the embodiment of the present invention described above, in which the transmission unevenness is suppressed, can be manufactured. Note that, although this manufacturing method has been described as being based on the online CVD method, even when the glass substrate or other main material previously manufactured by the float method or the like is heated by the offline method to form the film by the thermal CVD method, the transmission unevenness can be similarly suppressed by forming the visible light absorption layer using two or more coaters.

[0146] The method for producing a film-coated substrate of the present invention may further include a step of air-cooling or chemically strengthening the glass substrate (strengthening step). This strengthening step may be performed in any order, for example, before step S1 or after producing the film-coated substrate. By carrying out the strengthening step, the strength of the glass substrate and further the obtained film-coated substrate can be increased.

[0147] In addition, after the film is disposed on the glass substrate, the obtained film-coated substrate may be subjected to bending processing.

[0148] Alternatively, a laminated glass can be obtained by laminating the film-coated substrate of the present invention, an interlayer film, and an outer glass plate in this order.

[0149] It will be apparent to those skilled in the art that various other modifications are possible.

[0150] The film-coated substrate of the present invention can be used, for example, as vehicle window glass (front glass, rear glass, side glass, roof glass, etc.), building window glass, etc. In particular, a laminated glass provided with the film-coated substrate of the present invention is suitable for a panoramic roof. EXAMPLES

[0151] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these. Among the examples prepared below, Examples 5 and 6 are examples, and Examples 1 to 4 are comparative examples.

[0152] (Measurement of thickness of each layer) The substrate with the film was cut in the thickness direction, and the cross section was observed with a scanning electron microscope (SEM, "SU 70" manufactured by Hitachi, Ltd.). When the interface of the visible light absorption layer could be confirmed by SEM observation, the film thickness of each layer was directly examined from the SEM image. When the interface had unevenness, the film thickness of each layer was derived using the midline between the horizontal lines of the lowest valley and the highest peak as a guide. There is an appropriate range for the observation magnification, because if it is too low, the accuracy of the film thickness measurement becomes insufficient, while if it is too high, local unevenness is seen and the film thickness of each layer may not be derived correctly. Therefore, as a guideline for the observation conditions, an electron gun of 1.5 kV, a working distance of 2.4 mm, and a magnification of 50,000 times were adopted. When the interface of the visible light absorption layer could not be confirmed by SEM observation, it was examined by depth direction analysis using X-ray photoelectron spectroscopy (XPS). -6XPS measurements were performed while etching the film using Ar sputtering in an XPS chamber at 10 Pa. The X-ray irradiation area was fixed at 100 μmφ, and the X-ray irradiation angle was fixed at 45 deg. In this example, the optical adjustment layer was a SiOC film, so the cross point where the molar ratios of Sn and Si were the same was set as the interface between the visible light absorption layer and the optical adjustment layer. In deriving the molar ratio of each atom, the composition was calculated from the X-ray peak intensity using ULVAC's software PHI MULTIPAC. As XPS analysis conditions, electronic information of O1s, Si2p, Sn3d5, and Sb3d3 orbitals was referenced, but since O1s overlaps with the peak appearance position of Sb3d5, in deriving the molar ratio of each atom, calibration was performed by subtracting 1.5 times the Sb3d3 peak intensity from the O1s peak intensity in accordance with the principle. For XPS, a "PHI 5000 Versa Probe" manufactured by ULVAC-PHI was used.

[0153] (Measurement of antimony (Sb) concentration) The antimony concentration was analyzed in the depth direction by X-ray photoelectron spectroscopy (XPS) and examined from the intensity ratio of Sb and Sn. For XPS, a "PHI 5000 Versa Probe" manufactured by ULVAC-PHI was used. The XPS analysis method was the same as that for evaluating the thickness of each layer. Figure 2 (a) shows the XPS measurement results of Example 1, (b) shows the XPS measurement results of Example 5, and (c) shows the XPS measurement results of Example 6. From the impurity concentration distribution in the film thickness direction, the number of peaks at which the impurity concentration was maximum was found for each example. As a result, one peak was confirmed in Examples 1 to 4, and two peaks were confirmed in Examples 5 and 6. The antimony concentration in the visible light absorbing layer was determined by averaging the concentration in the depth direction measured by X-ray photoelectron spectroscopy (XPS).

[0154] (Transmittance measurement) From the transmission spectrum measured using PerkinElmer's "Lambda 1050", the visible light transmittance (T va , A light source transmittance) were calculated. T e was calculated based on the definition in JIS R3106 (2019).va was calculated based on the definition of the standard A light source. L was calculated based on ISO 9050:2003.

[0155] (Contrast ratio) The contrast ratio was determined using a commercially available camera and image analysis software (ImageJ) in the following manner. FIG. 6 is a diagram for explaining a method of photographing a sample to obtain a contrast ratio. The specific positional relationship between the film-coated substrate 30, the camera 31, and the surface light source (backlight) 32 was as shown in FIG. 6. The surface light source 32 was installed on a desk 33 in a darkroom, tilted 24° from the surface of the desk 33. The surface light source 32 used was a surface light source with an in-plane illuminance of 6000 to 10000 LUX (illuminance measuring device: TASCO digital illuminance meter ILLUMINATION METER TMS870). The film-coated substrate 30 was placed on the surface light source 32 so that the surface of the main material side of the film-coated substrate 30 was in contact with the surface light source 32, and the portion where the film-coated substrate 30 was not placed and the surface light source 32 was exposed was covered with a black cloth or the like to prevent excess light. A transmission image was photographed by the camera 31 from a location 600 mm away from the film-coated substrate 30. In this case, in order to improve the accuracy of the image analysis described below, a camera with an appropriate image sensor was used with a resolution of 0.2 mm / pixel or less for the captured image. The shutter speed during shooting was set to 1 / 10 or more, and the lowest shutter speed at which flicker did not occur. The aperture value was F1.4 or less, the ISO sensitivity was 100, and the camera was fixed to a tripod and a remote shutter was used to reduce the effects of camera shake. The images thus obtained were subjected to image analysis to determine the average luminance and contrast ratio. The image analysis was carried out as follows. First, the captured image was converted to grayscale (8bit: 256 gradations). Next, an analysis target region (hereinafter, ROI) of 1.0mm ± 0.5mm vertically and 150mm ± 50mm horizontally was set. The horizontal direction in this ROI is the direction that can include as much of the above-mentioned uneven transmission as possible. For example, in the case of vertical stripes, the direction perpendicular to the stripes is set as horizontal. The average of the luminance in this ROI was set as the average luminance. Furthermore, the luminance distribution in the horizontal direction of the ROI was calculated, and the standard deviation σ of the luminance distribution obtained by applying a bandpass filter was calculated. Here, the bandpass filter was set to leave wavelengths from 1.4mm to 50.0mm. From the above average luminance and the above standard deviation, {(average luminance + 3σ) / (average luminance - 3σ)}-1 was calculated, and this was set as the contrast ratio.

[0156] (Example 1) A film-attached substrate was prepared by the following method. Coaters for depositing each layer were placed inside the float glass manufacturing equipment, and a film-coated substrate was produced by the online CVD method. A SiOC layer was formed as an optical adjustment layer on the glass ribbon with the first coater, and an antimony-doped tin oxide film was formed as a visible light absorption layer with the second coater, to obtain a film-coated substrate in which the optical adjustment layer and the visible light absorption layer were laminated in that order on the main material. A turbulent coater was used as the second coater. The glass produced by the float glass production apparatus was a colorless and transparent glass substrate (soda-lime silicate glass) having a thickness of 2.1 mm.

[0157] First, 0.364 kg / hour of monosilane (SiH4), 0.25 kg / hour of ethylene, 12.5 kg / hour of CO2 gas, and 1.0 kg / hour of nitrogen gas were supplied from the first coater located at the most upstream side where the temperature of the glass ribbon was 760°C, and a SiOC layer with a thickness of 70 nm was formed on the glass ribbon.

[0158] Next, a visible light absorbing layer was formed on the SiOC layer. The raw material gases used were monobutyltin trichloride (C4H9SnCl3, MBTC), antimony trichloride (SbCl3), water, air, and hydrogen chloride, and the carrier gas was nitrogen. The molar ratio of each gas was MBTC:SbCl3:water:oxygen:hydrogen chloride:nitrogen=10:1:50:200:1:700. As a result, a film-attached substrate of Example 1 was obtained.

[0159] (Examples 2 to 4) A substrate with a film having the layer structure shown in Table 1 was produced in the same manner as in Example 1. The antimony concentration was adjusted by adjusting the raw material gas composition.

[0160] (Examples 5 and 6) A film-coated substrate having the layer structure shown in Table 1 was produced in the same manner as in Example 1, except that the coater configuration was changed as follows and the visible light absorbing layer was formed using two coaters. In Example 5, the second coater was a turbulent coater and the third coater was a laminar coater. In Example 6, both the second coater and the third coater were laminar coaters. First coater: Forms an optical adjustment layer (SiOC layer) Second coater: Forming a visible light absorbing layer (antimony-doped tin oxide film) Third coater: Forming a visible light absorbing layer (antimony-doped tin oxide film)

[0161] The film-coated substrates of each example were subjected to the above evaluations, and the results are shown in Table 1.

[0162] [Table 1]

[0163] From the results in Table 1, it was confirmed that in Examples 5 and 6, in which the visible light absorbing layer was formed using two or more coaters, the contrast ratio of the film-coated substrate was suppressed and transmission unevenness was suppressed, compared to Examples 1 to 4, in which the visible light absorbing layer was formed using one coater. [Explanation of symbols]

[0164] 1 Main material 1a First Side 1b Second Side 2 membrane 3 Visible light absorbing layer 5. Infrared reflective layer 7 Optical adjustment layer 10, 20 Film-coated substrate 52 Float Bus 53 Sealing Gate 54 Annealing furnace 55 Transport roller 56 Electric heater 60 Coater 70 Glass Ribbon

Claims

1. A film-attached substrate comprising a main material and a film disposed on the main material, the main material is glass, the main material has a first surface and a second surface opposed to each other, and the film is located on the first surface of the main material; The film includes a visible light absorbing layer made of a doped metal oxide doped with an impurity element, A film-attached substrate, wherein when the impurity concentration distribution in the film thickness direction of the visible light absorption layer is measured by X-ray photoelectron spectroscopy, two or more peaks at which the impurity concentration is maximized are confirmed.

2. The film-coated substrate according to claim 1 , wherein the visible light absorbing layer is an antimony-doped tin oxide film.

3. The film-coated substrate according to claim 1 , wherein the film-coated substrate has a light source A transmittance of less than 30%.

4. A method for producing a film-coated substrate, comprising forming a film on a base material, the main material is glass, and in forming the film, a visible light absorbing layer is formed by a thermal CVD method on a production line of the glass, depositing the visible light absorbing layer using two or more coaters; A method for producing a film-coated substrate.

5. The method for producing a film-coated substrate according to claim 4 , wherein the visible light absorbing layer is made of a doped metal oxide doped with an impurity element.

6. The method for producing a film-coated substrate according to claim 4 or 5, wherein the obtained film-coated substrate has a light source A transmittance of less than 30%.

Citation Information

Patent Citations

  • Method for manufacturing layered-film-bearing glass substrate

    WO2013008894A1

  • Glass substrate with laminated film and manufacturing method therefor

    WO2014112482A1

Cited By

  • Base material with film, windowpane for vehicle, and method for manufacturing base material with film

    WO2025239125A1